Mikrochirurgische Gefäßnaht - Mengen, Lilly; Horch, Raymund E.; Arkudas, Andreas (Operative Orthopadie und Traumatologie, 2024)
Objective: Anastomosis of two vessels by end-to-end or end-to-side suturing to create an uninterrupted blood flow between the two vessels. Indications: Transplantations; replantations; vascular trauma. Contraindications: Active infections in the area to be vascularized or surgical site; large differences in caliber between the vessels; hypercoagulability; extensive tissue damage. Surgical technique: First, clamping, cleaning and flushing of the vessel ends; adaptation of the vessel ends using end-to-end or end-to-side anastomosis, using an end-to-side anastomosis if an existing vessel axis should not be interrupted; creation of the anastomosis using a single button suture or continuous suture technique; careful avoidance of puncturing the posterior wall and exact adaptation of the vessel ends without leaks; release of the blood flow and examination of the anastomosis. Postoperative management: Postoperative avoidance of traction, tension, pressure and shear forces on the anastomosis; regular blood flow checks of the revascularized tissue or flap; sufficient anticoagulation. Results: An atraumatic and gentle suturing technique is a basic requirement for a successful anastomosis. Special suturing techniques can improve the anastomosis of fragile vessels.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Continuous suture technique; End-to-end anastomosis; End-to-side anastomosis; Single-button suture; Vascular suture

Schwann Cells Do Not Promote Myogenic Differentiation in the EPI Loop Model - Xu, Zhou; Arkudas, Andreas; Munawar, Muhammad; Schubert, Dirk W.; Fey, Tobias; Weisbach, Volker; Mengen, Lilly; Horch, Raymund E.; Cai, Aijia (Tissue Engineering - Part A, 2024)
In skeletal muscle tissue engineering, innervation and vascularization play an essential role in the establishment of functional skeletal muscle. For adequate three-dimensional assembly, biocompatible aligned nanofibers are beneficial as matrices for cell seeding. The aim of this study was to analyze the impact of Schwann cells (SC) on myoblast (Mb) and adipogenic mesenchymal stromal cell (ADSC) cocultures on poly-e-caprolactone (PCL)collagen I-nanofibers in vivo. Human Mb/ADSC cocultures, as well as Mb/ADSC/SC cocultures, were seeded onto PCL-collagen I-nanofiber scaffolds and implanted into the innervated arteriovenous loop model (EPI loop model) of immunodeficient rats for 4 weeks. Histological staining and gene expression were used to compare their capacity for vascularization, immunological response, myogenic differentiation, and innervation. After 4 weeks, both Mb/ADSC and Mb/ADSC/SC coculture systems showed similar amounts and distribution of vascularization, as well as immunological activity. Myogenic differentiation could be observed in both groups through histological staining (desmin, myosin heavy chain) and gene expression (MYOD, MYH3, ACTA1) without significant difference between groups. Expression of CHRNB and LAMB2 also implied neuromuscular junction formation. Our study suggests that the addition of SC did not significantly impact myogenesis and innervation in this model. The implanted motor nerve branch may have played a more significant role than the presence of SC.
CRIS-Team Scopus Importer:2024-02-16
Keywords: electrospun nanofibers; EPI-loop; mesenchymal stromal cells; myoblasts; myogenic differentiation; schwann cells

Selection of optimal human myoblasts based on patient related factors influencing proliferation and differentiation capacity - Englich, Moritz; Arkudas, Andreas; Mengen, Lilly; Horch, Raymund E.; Cai, Aijia (Scientific Reports, 2025)
Human myoblasts (hMb) are a promising source for engineering skeletal muscle tissue. But sample-specific variabilities make research with human cells challenging. For the purpose of selecting hMb with adequate proliferation and differentiation properties, the influence of various patient related factors, including age, gender, BMI, anatomical sampling site and previous radio-/chemotherapy on hMb behavior was investigated in this study. Immunofluorescence staining and proliferation periods were analysed for proliferation capacity, while creatine kinase and cell viability assay, immunofluorescence staining and PCR were used to determine differentiation capacity. Using desmin expression, a multiple linear regression (MLR) model was established based on the above-mentioned patient related factors. Higher age and BMI, female gender and chemotherapy had a negative impact on desmin expression. Muscle type specific differences could also be seen. Previous radiotherapy led to senescence of hMb in large parts. Differentiation was mainly influenced by gender in a time-dependent manner, as well as by the anatomical collecting site. We were able to demonstrate the importance of analyzing patient characteristics for the purpose of hMb isolation. Using MLR, these patient characteristics can be used to predict the proliferation capacity of hMb as a step further towards translational application of skeletal muscle engineering and regeneration.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Multiple linear regression; Myoblast proliferation; Myoblasts; Myogenic differentiation; Skeletal muscle; Tissue engineering